2017
DOI: 10.3390/molecules22030372
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of the Lignins Derived from Fluidized-Bed Fast Pyrolysis

Abstract: A challenge in recent years has been the rational use of forest and agriculture residues for the production of bio-fuel, biochemical, and other bioproducts. In this study, potentially useful compounds from pyrolytic lignins were identified by HPLC-MS/MS and untargeted metabolomics. The metabolites identified were 2-(4-allyl-2-methoxyphenoxy)-1-(4-hydroxy-3-methoxyphenyl)-1-propanol, benzyl benzoate, fisetinidol, phenyllactic acid, 2-phenylpropionic acid, 6,3′-dimethoxyflavone, and vanillin. The 2,2-diphenyl-1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 39 publications
(44 reference statements)
0
20
0
Order By: Relevance
“…Among all HP-EOL samples, samples 2, 4, 6 and 8 showed the highest total phenolic content which was up to 25.6 mg GAE/g, indicating that the total phenolic content of lignin was remarkably improved by ethanol concentration (60% w/v). Qazi et al [37] reported total phenolic content values of pyrolytic Kraft lignins between 0.42 and 50 mg GAE/g. On the other hand, An et al [35] achieved up to 246.13 mg GAE/g for lignin from corn straw recovered from a residue pretreated by steam explosion and enzymatic hydrolysis, and purified using a dioxane extraction process and dichloromethane fractionation.…”
Section: Total Phenolic Content and Antioxidant Activities Of Ligninsmentioning
confidence: 99%
“…Among all HP-EOL samples, samples 2, 4, 6 and 8 showed the highest total phenolic content which was up to 25.6 mg GAE/g, indicating that the total phenolic content of lignin was remarkably improved by ethanol concentration (60% w/v). Qazi et al [37] reported total phenolic content values of pyrolytic Kraft lignins between 0.42 and 50 mg GAE/g. On the other hand, An et al [35] achieved up to 246.13 mg GAE/g for lignin from corn straw recovered from a residue pretreated by steam explosion and enzymatic hydrolysis, and purified using a dioxane extraction process and dichloromethane fractionation.…”
Section: Total Phenolic Content and Antioxidant Activities Of Ligninsmentioning
confidence: 99%
“…Natural plant polyphenols are promising in this regard; they protect healthy tissues, in particular decreasing production of intracellular ROS, but do not diminish the effect of chemotherapies (9). Notably, not only low-molecular weight polyphenols exhibit antioxidant efficacy, but polymeric polyphenolic compositions, such as lignin derivatives, exert it too (10).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it may have similarities with biochar and hydrochar, and can provide the base material for the production of adsorbents [165]. Phenolic oligomers from bio-oils were suggested as potential fuel antioxidants [105,107,108]. As sCO 2 extracts preferentially phenolic monomers, the residue is expected to be enriched in these components.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the antioxidant activity of bio-oil fractions has been studied for both pyrolysis and HTL oils derived by different biomasses [105][106][107][108]. Phenolic dimers and oligomers are suggested as the active antioxidant components, as monomers exhibited small to no antioxidant activity.…”
Section: Production Of Green Chemicalsmentioning
confidence: 99%